0162 Zeitgebers And Their Association With Rest-activity Patterns. (27th April 2018) - Quante, M; Mariani, S; Weng, J; Marinac, C; Kaplan, E; Rueschman, M; Mitchell, J; James, P; Hipp, J; Cespedes Feliciano, E; Wang, R; Redline, S
Abstract: Introduction: Environmental cues (zeitgebers) provide input to the circadian clock. Chronic circadian misalignment is associated with significant adverse health effects. Improved understanding of the impact of the timing of zeitgebers on the stability of 24-hour rest-activity rhythm in free-living settings may identify behavioral and environmental intervention targets. Methods: 133 healthy adults, (21 - 60 years), wore a wrist actigraph for 7 consecutive days. We applied the cosinor model and non-parametric analysis to activity counts to derive rest-activity patterns. We administered a questionnaire through a smartphone app to collect the timing of light exposure, eating episodes and physical activity. To assess the relationship between zeitgebers and rest-activity outcomes, we first calculated Spearman correlations, using the false discovery rate method to control for multiple comparisons. From those significant associations we then ran regression models adjusting for age, sex, race, household income, education level, study site, BMI, and physical activity. Finally, we tested for interaction between chronotype (from questionnaire) and each timing-related exposure and stratified the analysis by morning type. Results: All zeitgebers, except for evening physical activity proportion, were correlated with at least 5 of the 10 sleep and rest-activity outcomes. In adjusted analysis, later timing of first and last exposure to indoor light and first and last eating episode were positively associated with bed times, M10 and L5 midpoints (i.e. timing of peak activities or inactivities). Later timing of first exposure to outdoor light also associated with longer sleep duration and lower mean activity level (MESOR). Higher morning physical activity proportion predicted earlier in- and out-of-bed times, acrophase, and M10 and L5 midpoints. There was significant interaction between morning chronotype and first eating episode and rest-activity patterns, (p<0.05), with first eating episode associated with timing of activities only in non-morning type adults. Conclusion: Timing of zeitgebers was associated with measures of circadian phase and timing of rest-activity patterns, including bed-times, acrophase, L5 and M10 midpoint. Future research should evaluate the impact of manipulating zeitgebers on both circadian rhythms and associated health outcomes. Support (If Any): NCI grants U01CA116850, U54CA155496, U54CA155626, U54CA155435, U54CA155850 and R00CA201542.